Single mothers' income in twelve rich nations: Differences in disadvantage across the distribution - Susan Harkness (University of Essex, Institute for Social and Economic Research (ISER), 2022)
I examine how single motherhood affects income at different quantiles of the distribution in twelve rich countries. Using harmonised data from the Luxembourg Income Study, I show how the distribution of income for single-mother headed households differs to that of coupleheaded households with children. Using unconditional quantile treatment effect models, I assess the influence of single motherhood on income at different points of the distribution. There are striking variations across countries in how single motherhood affects income at different points of the distribution. In some countries, such as the United Kingdom, single motherhood has a greater effect on income at the top of the distribution than the bottom. In others, such as the United States, effects are largest at the bottom of the distribution. I discuss the role of employment and social policies in driving differences in the income gradient associated with single motherhood across the distribution across countries.
Keywords: 330; single mothers; inequality; quantile treatment effects; tax and benefits; employment